Monsters love underpants - Freedman, Claire; Cort, Ben (New York : Aladdin Books, 2015)
"Monsters all over the world have different ways to scare, but they all have one thing in common: they all love zany underpants! And every Saturday night, you will find them in a secret cave, showing off their fancy pants as they dance the Monster Bop! But they have to make it home before the sun comes up--after all, who would be scared of monsters in underpants that are striped and dotted? Readers will love this playful and rollicking romp in the latest Underpants book from Claire Freedman and Ben Cort"--Jacket.